ON THE RELATIONSHIP BETWEEN STRUCTURE AND THERMAL STABILITY PROPERTIES OF COPPER CLUSTERS SIZE UP TO 100 ATOMS IN MOLECULAR-DYNAMICS SIMULATION - V.S. Myasnichenko; P.M. Ershov; N.Yu. Sdobnyakov; D.N. Sokolov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2015)
In this paper a molecular-dynamics simulation of the structure and thermal stability of the copper clusters size up to 100 atoms has been carried out using many-body tight-binding potential. On the basis of the calculation of a local minimum energy for copper clusters it the «magic» nanoclusters can be found which are more stable. The size dependencies of the thermodynamic and structural characteristics for such clusters demonstrate specific behavior.